PENERAPAN ALAT PERMAINAN EDUKATIF SENSORY PATH DALAM MENINGKATKAN ASPEK PERKEMBANGAN KOGNITIF ANAK KELOMPOK A (USIA 4-5 TAHUN) DI TK PGRI 3 NGAWI DS. MANGUNHARJO KEC. NGAWI KAB. NGAWI - Anita Solihatul Wahidah; Indri Sulistyani (Kurikula : Jurnal Pendidikan, 2022)
ABSTRACT Educational Game Tool (APE) is a learning media with the aim of improving the ability of aspects of child development that are tailored to the age and level of child development in an interesting way. APE that can be used to improve aspects of child development with the sensory path. Sensory Path is a sensory pathway that was developed into an educational play tool to develop children's development that involves the five senses, one of which is children's cognitive abilities related to memory, logical thinking and problem solving. Low cognitive abilities and the lack of learning media used make children less interested and bored in following the learning delivered. This problem is the background of research on the application of sensory path educational game tools in improving aspects of cognitive development of children in group A (aged 4-5 years) at PGRI 3 Ngawi This study uses a qualitative approach with the type of Classroom Action Research (CAR) where data is collected by interview, observation and documentation methods. Sources of informants from this study were the principal and educators of PGRI 3 TK in Ngawi. The results of this study will be presented in the form of sentences, not in the form of numbers presented in the observation table. The data analysis technique used is observation, assessment sheet and conclusion drawing. With learning that applies the Sensory Path Educational Game Tool, it can be seen that there is an increase in children's cognitive abilities which can be seen from the initial condition of the child's cognitive ability which was originally still quite low with conditions after the application of the sensory path educational game tool to increase. The application of sensory path educational games has been proven to improve cognitive abilities in children aged 4-5 years. Keywords: Educational Game Tool (APE), Sensory Path, Cognitive Aspect